Heteronormative beliefs and the impact on self-acceptance and disclosure of male homosexuality in Portugal and Turkey - Torres Rosado, César Alexander (2019)
Several studies have shown that heteronormative contexts are detrimental to the process of sexual identity development of non-heterosexuals. However, research examining how internalizing heteronormativity can affect the coming-out process of gay individuals is still scarce. Therefore, we argue that that internalization of heteronormativity and homonegativity (sexual prejudice against homosexuality) could have crucial roles in the coming-out process. Thus, the present study focuses on how socially imposed heteronormative beliefs are associated with the coming-out process, specifically with the selfacceptance and disclosure of homosexuality among gay men, and if this association is mediated by homonegativity. We conducted a cross-sectional survey study with 396 men that are romantically/sexually attracted to other men living in Portugal (n = 247; Mage = 28.10, SD = 9.94) and Turkey (n = 149; Mage = 24.80, SD = 7.73). Results confirmed the hypothesized model. Indeed, greater heteronormative beliefs were associated with lower levels of selfacceptance and disclosure of homosexuality, and this association was partially mediated by homonegativity levels. Furthermore, results showed that this mediation differed depending on the country. For the Portuguese sample, the association between heteronormative beliefs and self-acceptance and disclosure was weaker than in the Turkish sample, but the overall mediation through homonegativity was stronger. These findings showed that the internalization of heteronormative beliefs plays an important role in the coming-out process of gay men. Overall, this research makes innovating contributions to the existing literature on gay identity development, gay-affirmative psychology, and LGBTI+ activism